APOE‐ε4 carriers have superior recall on the 'What was where?' visual short‐term memory binding test at age 70, despite a detrimental effect of β‐amyloid: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Lu, Kirsty; Nicholas, Jennifer M.; Pertzov, Yoni; Grogan, John; Husain, Masud; Pavisic, Ivanna M.; James, Sarah‐Naomi; Parker, Thomas D.; Lane, Christopher A; Keshavan, Ashvini; Keuss, Sarah E.; Buchanan, Sarah M.; et al.
Abstract: Background: While APOE ‐ε4 carriers are at higher risk of Alzheimer's disease (AD), there is evidence that APOE ‐ε4 may have some beneficial effects across the life‐span, including on cognition. It is unclear how such effects may relate to subtle memory decline during the preclinical phase of AD. Two previous studies reported that APOE ‐ε4 carriers recalled object locations more accurately than non‐carriers on the "What was where?" visual short‐term memory binding test (10.1016/j.cortex.2016.12.016; 10.1016/j.neurobiolaging.2018.09.017), but these studies did not account for preclinical AD pathology. Method: The "What was where?" task (Figure 1) was administered to participants in Insight 46 – a sub‐study of the British 1946 birth cohort – who were all born during the same week (aged 69‐71 at assessment (Table 1)). Outcomes included object identification and a sensitive analogue measure of localisation error (the distance between the location reported by the participant and the true location). Two‐dimensional mixture models (10.31234/osf.io/q57fm) were used to isolate three sources of localisation error: imprecision, guessing, and misbinding (swapping an object's location with that of a different object). β‐Amyloid status (positive / negative) was determined from 18 F‐Florbetapir‐PET. Multivariable regression models were used to investigate differential effects of APOE genotype (ε4‐carrier / non‐carrier) and β‐amyloid status on performance in 398 cognitively‐normal participants, adjusting for confounders including a prospectively‐collected measure of childhood cognitive ability. Result: APOE ‐ε4 and β‐amyloid had opposing effects on object identification, with APOE ‐ε4 predicting better recall and β‐amyloid‐positivity predicting poorer recall. APOE ‐ε4 carriers also recalled object locations more precisely, but a subtle detrimental effect of β‐amyloid on localisation was seen only among non‐carriers (Table 2, Figure 2). Childhood cognitive ability also predicted performance over 60 years later (Table 2). Conclusion: In this large population‐based sample of cognitively‐normal ∼70‐year‐olds, a positive association between APOE ‐ε4 and short‐term visual memory was observed. For the localization measure, this appeared to be protective against a subtle deficit associated with β‐amyloid pathology. This is consistent with the antagonistic pleiotropy hypothesis – whereby a gene controls both beneficial and detrimental traits – and provides novel evidence that these effects persist into older age, even among individuals who may be in the preclinical stages of AD.